Mosquito-borne Flaviviruses : Vector and Avian Host Susceptibility for West Nile Virus and Usutu Virus in Germany - Holicki, Cora (Tierärztliche Hochschule Hannover, 2020)
Flaviviruses are known to cause a variety of diseases in humans as well as animals, ranging from mild febrile illnesses to severe hemorrhagic or neuroinvasive manifestations. West Nile virus (WNV) and Usutu virus (USUV) are closely related flaviviruses circulating in an enzootic sylvatic cycle, consisting of mosquitoes (particularly Culex species) as vectors and birds as amplifying and/or reservoir hosts. Humans and equines, however, are considered dead-end hosts as they can develop severe clinical diseases but cannot in turn infect naïve feeding mosquitoes. Globalization, with increased international trade, in combination with climate change is facilitating the worldwide spread of vectors and their pathogens. To date WNV is the most dispersed zoonotic arbovirus, with detections in every continent aside Antarctica. Outbreaks are recorded yearly and the virus is becoming an increasing veterinary and public health concern. At the same time, USUV is also expanding its geographical range and colonizing new ecological niches. Since the first isolation of USUV (2010) and WNV (2018) in Germany, both viruses have become endemic. They are overwintering either in infected mosquito females or in natural reservoir hosts with a yearly reemergence predominantly towards the end of the mosquito transmission seasons (from August to October). This has not only emphasized the necessity for evidence-based passive and active surveillance programs, but also for the completion of infection studies focusing on the pathogenesis of these viruses and the immunocompetence of their hosts. The experiments in the frame of this thesis, therefore, began to uncover vector species involved in the WNV and USUV transmission cycles in Germany and to tackle the question of whether domestic poultry could play a role as an amplifying and/or reservoir host for WNV. In the first study (manuscript I) German Cx. pipiens biotype molestus and Cx. torrentium species proved to be vector-competent for an USUV Africa lineage 2 strain, isolated in Germany from a ...